Who are the Elis of Today? Examining the Adults Present During the Religious Identity Development of Catholic-Raised Youth - Vaclavik, Danielle S (2018)
Given that a large percentage of former-Catholic adults report leaving the Church before reaching adulthood, and the percentages of Catholic-raised youth retaining their religious identity into adulthood are decreasing, a pressing question currently facing the modern Catholic Church is how to minister to, and retain, Catholic-raised adolescents into adulthood. Current religious and secular literature suggests that adults (both parental and non-parental) may play a crucial role in youths’ religious identity development. However, who these adults are and how their presence influences the experience of growing up Catholic is unexplored in the current literature. In depth oral history narrative interviews were conducted with 24 Catholic-raised young adults; 12 who identify as Currently-Catholic and 12 who identify as Previously-Catholic. During these interviews, participants were asked to describe their experiences growing up Catholic and how they arrived at their current religious identity. Participants were also asked to focus their narrative on the adults they believe played a role in their religious identity development. Transcribed interviews were coded using modified grounded theory open coding strategies. Results include a list of adults present during the religious identity development process of Catholic-raised youth and themes related to characteristics and behaviors common to these adults. In addition, comparisons were drawn between types of adults, adult characteristics and adult behaviors between the two religious identity groups. In total, the 24 participants described 275 adults (M = 12.54 per participants, range = 3-20) during their interviews. Qualitative analysis fit these adults into six adult types: family adults, parish adults, school adults, religious event adults, large groups/communities of adults, and other adults (i.e., adults not met in any of the previous five settings). When discussing the adults present in their religious identity narratives, the characteristics participants felt influenced their religious identity development fell into four thematic categories: intelligence/lacking knowledge, engaging/ unengaging personality, approachable/unapproachable, and authentic/ disingenuous. Finally, behaviors participants felt influenced their religious identity development fell into six thematic categories: provided unconditional support versus conditional support, facilitated/had discussions about religion versus lacked/discouraged religious conversations, taught about the Catholic religion versus taught incorrect religious information, did or did not model a Catholic lifestyle, respected or disrespected other religions, and connected youth to Catholic experiences/people versus negative connections to Catholic activities. Quantitative analysis using the Mann-Whitney-U test found Currently-Catholic mentioned a significantly higher median number of religious event adults than their Previously-Catholic counterparts. Currently-Catholics also mentioned a significantly higher median number of adults who exhibited the authentic personality characteristic while Previously-Catholic participants mentioned a significantly higher median number of adults who exhibited the unapproachable personality characteristic. Currently-Catholic participants mentioned significantly higher median numbers of adults who exhibited the positive behavior: facilitated/ had discussions about religion. Previously-Catholic participants mentioned significantly higher median numbers of adults who exhibited the negative behaviors: provided conditional support, lacked/discouraged religious conversations, did not model a Catholic lifestyle, and negative connections to Catholic activities. This dissertation aimed to add to the limited literature regarding the religious identity formation of Catholic-raised youth, inform educational ministry and outreach strategies, and discuss the applicability and similarities of secular supportive adult behaviors in a religious setting